High cellphone use associated with greater risk of depression among young women aged 15–24 years in Soweto and Durban, South Africa. Issue 1 (1st January 2021) - Dietrich, Janan J.; Otwombe, Kennedy; Pakhomova, Tatiana E.; Horvath, Keith J.; Hornschuh, Stefanie; Hlongwane, Khuthadzo; Closson, Kalysha; Mulaudzi, Mamakiri; Smith, Patricia; Beksinska, Mags; Gray, Glenda E.; Brockman, Mark; et al.
ABSTRACT: Background: The ubiquity of cellular phone (cellphone) use in young people's daily lives has emerged as a priority area of concern for youth mental health. Objective: This study measured the prevalence of depression and its association with high cellphone use among youth in Soweto and Durban, South Africa. Methods: We analysed cross-sectional, baseline survey data among youth aged 16–24 who participated in a dual-site cohort study, 'AYAZAZI', conducted from 2014 to 2017. The primary outcome was depression using the 10-item Center for Epidemiologic Studies Depression Scale, with a score of ≥ 10 indicating probable depression. Cellphone use was measured via self-reported average number of hours of active use, with 'high cellphone use' defined as daily usage of ≥ 8. Multivariable logistic regression models assessed the independent relationship between high cellphone use and probable depression, adjusting for potential confounders. Results: Of 425 participants with a median age of 19 years (IQR = 18–21), 59.5% were young women. Overall, 43.3% had probable depression, with a higher prevalence among women (49.0% vs. 34.9%, P = .004). Nearly all (94.6%) owned a cellphone. About one-third (29.5%) reported spending ≥ 8 hours per day using their cellphone (39.3% of women vs. 14.9% of men, P < .001). In the overall adjusted model, youth reporting high daily cellphone use had higher odds of probable depression (aOR: 1.83, 95% CI: 1.16–2.90). In gender-stratified models, high daily cellphone use was associated with probable depression among women (aOR: 2.51, 95% CI: 1.47–4.31), but not among men (aOR: 0.87, 95% CI: 0.35–2.16). Conclusions: Among a cohort of South African youth, we found a high prevalence of probable depression and high cellphone use (30%). The findings indicate a need for intersectoral initiatives focused on meaningful mental health support for South African youth to support positive growth and development.